A Bibliography of Legal Festschriften
189 p.
Keywords: The idea of compiling a bibliography of legal Festschriften originated with Lilly Roberts, and represented the most important creative side of her life during the last ten years of her association with the Universi ty of Michigan Law Library. The project received advice and counsel from the Foreign Law Com mittee of the American Association of Law Libraries. The final publi cation was made possible by an allocation from the grant made to the University of Michigan Law School by the Ford Foundation for re search in International and Comparative Law. Beverley J. Pooley Professor of Law Director of the Law Library University of Michigan PREFACE The present bibliography is international in scope; it covers Fest schriften published in many countries. It includes Festschriften from 1868 (date of the earliest legal Festschrift found) through December, 1968. A bibliography of all legal Festschriften, to be complete, could only be achieved through the cooperative effort of an international group of experts. The present bibliography is based on notes gathered by the compiler over a period of years from material available at the University of Michigan Law Library. It is therefore, inevitably, incom plete and occasionally inaccurate and must be considered as a tentative list, subject to implementation and correction at other legal centers. It was felt, however, that its publication might be of some use, since not enough bibliographical information about this important and steadily growing type of legal literature exists.